The zimzum of love : a new way of understanding marriage - Bell, Rob, 1970- (HarperOne, an imprint of HarperCollinsPublishers, 2014)
"Despite the divorce statistics, people are still committing to each other, instinctively believing and hoping that theirs is a sacred union that will last forever. Yet when these couples encounter problems, they often lack the resources that keep them connected to this greater mystery surrounding marriage. Rob and Kristin Bell introduce a startling new way of looking at marriage, The Zimzum of Love. Zimzum is a Hebrew term where God, in order to have a relationship with the world, contracts, creating space for the creation to exist. In marriage, zimzum is the dynamic energy field between two partners, in which each person contracts to allow the other to flourish. Mastering this field, this give and take of energy, is the secret to what makes marriage flourish. Rob and Kristin Bell are brutally honest about their own struggles, their ups and downs, as together they pass along what matters most for couples. In this wise book, they explore the secret of what makes a happy union-- probing the mystery at the heart of the extraordinary emotional connection that binds two people." "--